Food allergy. Part I – Cow’s milk - Rudzki, Edward (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2005)
In the paper the following questions are discussed: allergenicity of cow’s milk proteins; cross reactions between milk proteins from different animal species; cow’s milk sensitivity in children and adult patients and usefulness of oral challenge tests in the diagnostics of cow’s milk allergy.